The effect of cassava mosaic disease on growth and yield of a local and an improved variety of cassava - Terry, E.R.; Hahn, S.K. (1980)
The improved cassava mosaic-resistant cassava variety TMS 30395 produced significantly higher root yields under field conditions than its susceptible parent Isunikakiyan, irrespective of whether it was established from mosaic-free or mosaic-infected planting material. Significant reductions in fresh root yield, root number, root size, top fresh weight and starch content in both varieties resulted from plants established from CMD-infected planting material. For the variety Isunikakiyan, yield reduction was greater in plants established from clonal CMD-infected cuttings than in those established from disease-free cuttings but which later became infected through vector transmission.